2015
DOI: 10.1016/j.radi.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

An audit to investigate the impact of false positive breast screening results and diagnostic work-up on re-engagement with subsequent routine screening

Abstract: Introduction: Women attending breast screening may have suspicious mammographic findings that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…14 A retrospective six year audit undertaken within a UK breast screening service identified that the percentage of eligible FP women failing to re-engage with screening was considerably lower than non-engagement in the general screening population (15% compared to 29%). 3 However, those undergoing biopsies were more likely to return for routine screening than those undergoing minimally invasive assessment (93% compared to 82.5%). 3 This was at odds with published literature 12;14 and suggested that the additional support received by women having biopsies has a beneficial effect on their future re-engagement with screening.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…14 A retrospective six year audit undertaken within a UK breast screening service identified that the percentage of eligible FP women failing to re-engage with screening was considerably lower than non-engagement in the general screening population (15% compared to 29%). 3 However, those undergoing biopsies were more likely to return for routine screening than those undergoing minimally invasive assessment (93% compared to 82.5%). 3 This was at odds with published literature 12;14 and suggested that the additional support received by women having biopsies has a beneficial effect on their future re-engagement with screening.…”
Section: Introductionmentioning
confidence: 98%
“…3 However, those undergoing biopsies were more likely to return for routine screening than those undergoing minimally invasive assessment (93% compared to 82.5%). 3 This was at odds with published literature 12;14 and suggested that the additional support received by women having biopsies has a beneficial effect on their future re-engagement with screening. 3 A qualitative study was initiated to explore in detail the nature of staff-client interactions within a breast assessment clinic affiliated to the NHS Breast Screening Programme.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation